An immunohistological study of secondary Sjögren's syndrome. Issue 3 (June 1984) - Isenberg, D A; Rowe, D; Tookman, A; Hopp, A; Griffiths, M; Paice, E; Stewart, J; Beverley, P C
Abstract : The labial biopsies from 13 patients with secondary Sjögren's syndrome (SS) and four disease controls were examined with a panel of monoclonal antibodies to human leucocyte antigens. Large numbers of T cells were found in most of the biopsies. In seven SS patients the T helper/inducer subset was found to be predominant. Antibody to HLA class I antigens consistently stained leucocytes, but other cell types stained more variably. Although the staining with antibody to HLA class II antigen was often weak, approximately as many cells stained with this antibody as with an antileucocyte antibody, implying that the T cells were activated. Anti-IgD revealed membrane staining of a corona of IgD-positive cells in structures resembling germinal centres. Isolated cells throughout the sections also showed strong cytoplasmic staining with anti-IgD. These results suggest a role for T-cell-dependent local antibody synthesis in the pathogenesis of the disease.